RELASI BUDAYA ORGANISASI TERHADAP EFEKTIVITAS ORGANISASI PADA LEMBAGA PENDIDIKAN ISLAM DAN PONDOK PESANTREN - Akhmad Muadin (EDUTHINK: Jurnal Pemikiran Pendidikan Islam, 2020)
Organizational culture is often understood as a set of beliefs or values thatexist in the organization. It is also believed that the implementation of astrong organizational culture can bring out the characteristics and identityof an organization. It is also through this culture that public consumers canget to know the organization and then position the organization in theirminds. Because organizational culture contains a set of values that areembraced and practiced by all people in the organization, the role of religiousinstitutions or institutions is as an institution that is believed to be one ofthe sources of values or norms in society. With a good organizational culture,it is expected that the goals and objectives of the organization can be achievedoptimally. Building a strong culture requires strong leaders who have strongvisions and personalities. The founders are the people who build the vision,mission, philosophy and main goals of the organization. There was also atime when organizational behavior was initiated by the founders and othertop leadership teams